Method for synthesizing polypeptide drug molecules encapsulated by calcium phosphate nanoparticles through solvent phase separation
The method of synthesizing calcium phosphate nanoparticle encapsulated polypeptide drugs through solvent phase separation solves the problems of long reaction time and complex reaction system in the prior art, realizes a fast and efficient encapsulation process, and ensures high purification and biocompatibility of the product.
Patent Information
- Application Number
- CN202411761164.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The method for synthesizing calcium phosphate-encapsulated polypeptide drugs in the prior art has a long reaction time, a complex reaction system, and it is difficult to completely remove auxiliary substances, which affects the purification of the drug and the safety of in vivo application.
The method of synthesizing calcium phosphate nanoparticles encapsulated polypeptide drugs by solvent phase separation is adopted. The calcium phosphate nanoparticles are rapidly synthesized by adding sodium phosphate and calcium chloride to the water-ethanol solvent phase separation system, and the product is purified by washing with pure water.
The reaction system is simplified, the reaction time is shortened to 1 hour, the synthesis efficiency is improved, the product is highly purified and biocompatible, the polypeptide drug is effectively protected from external damage, and the safe delivery of the drug is achieved.
Smart Images

Figure CN119587507A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for encapsulating polypeptide drug molecules by synthesizing calcium phosphate nanoparticles through solvent phase separation, and belongs to the field of drug molecule encapsulation and nano drug preparation. Background Art
[0002] Peptide drugs are short-chain molecules composed of amino acids, usually composed of 20 to 50 amino acid residues. Their molecular weight is between small molecule drugs and protein drugs, which fills the gap between the two and becomes a new class of drugs. Peptide drugs have high specificity, low toxicity and good biocompatibility. They can target specific cells or molecular pathways and show great potential in the treatment of various diseases. Especially in the treatment of diabetes, many new peptide drugs have emerged, such as Liraglutide, Semaglutide, Tirzepatide, etc. These peptide drugs have shown certain effects in the clinical control and treatment of diabetes.
[0003] However, peptide drugs also face some challenges, among which the problem of peptide drugs being easily degraded by enzymes in the body and having poor stability is particularly obvious. In order to solve this problem, researchers have adopted various methods to improve the stability of peptide drugs. One of the methods is to encapsulate peptide drug molecules on a nanoscale to achieve the purpose of improving the stability of peptide drug molecules and prolonging the drug's action time.
[0004] Among the many nanomaterials used to encapsulate peptide drug molecules, calcium phosphate (CaP) has obvious advantages due to its high biocompatibility and biodegradability. The controllable solubility and biocompatibility of calcium phosphate allow it to gradually degrade in the biological environment, ensuring that non-toxic degradation products are safely metabolized, thereby supporting the sustained release of therapeutic agents in drug delivery applications. The current common method for synthesizing calcium phosphate encapsulated peptide drugs is mainly the mineralization method, which uses calcium ions to deposit on peptide molecules and eventually precipitate in the form of nanoparticles. However, this method has a long reaction time. More importantly, its reaction system often requires multiple substances for auxiliary synthesis. The reaction system is relatively complex, which is not conducive to subsequent purification and in vivo application. Summary of the invention
[0005] The technical problem solved by the present invention is: a method for encapsulating polypeptide drug molecules by synthesizing calcium phosphate nanoparticles by solvent phase separation is proposed, which can realize the rapid encapsulation of polypeptide drug molecules in calcium phosphate nanoparticles under a simple reaction system for subsequent drug delivery and treatment. The reaction system of calcium phosphate encapsulating polypeptide drug molecules in the traditional method is relatively complex, and a variety of substances are often required as auxiliary substances in its synthesis system, and these substances are difficult to be completely removed in the subsequent purification process. In the reaction system of the present invention, due to the property that sodium phosphate is easily soluble in water but insoluble in ethanol, sodium phosphate is used as a phase separation agent in the phase separation system and as a raw material for synthesizing calcium phosphate nanoparticles, which simplifies the reaction system to the greatest extent and is conducive to the purification of subsequent products. And the substances used in the synthesis method of the present invention have strong biocompatibility, which fundamentally guarantees the safety of the drug used in vivo. Calcium phosphate nanoparticles can effectively protect polypeptides and improve the stability of polypeptides. The calcium phosphate nanoparticles encapsulating polypeptide drug molecules synthesized by the present invention can also effectively protect polypeptide drugs from damage by the external environment, such as damage in an alkaline environment, damage under the presence of oxidants, and the like. However, the reaction time of calcium phosphate nanoparticles encapsulating polypeptide drug molecules is usually long, and the synthesis efficiency is low, which is not conducive to large-scale production. The synthesis method proposed in the present invention can encapsulate polypeptide drug molecules in calcium phosphate nanoparticles more quickly. In the traditional method of synthesizing calcium phosphate encapsulated polypeptide molecules, such as in the mineralization method, the reaction synthesis time is generally 3 hours or even more than 12 hours, while the reaction system of the present invention only takes 1 hour to complete the reaction, which greatly improves the synthesis efficiency of the reaction. By regulating the synthesis parameters, the synthesis ratio determined by the present invention can ensure a certain encapsulation rate on the basis of ensuring the particle morphology. At the same time, the present invention can be used as a safer and more efficient platform technology to encapsulate polypeptide molecules in calcium phosphate nanoparticles, and it is expected to be synthesized on a large scale in the future and used for drug delivery in the body.
[0006] The specific technical solution proposed by the present invention is: a method for synthesizing calcium phosphate nanoparticles encapsulating polypeptide drug molecules by solvent phase separation, the specific steps are as follows
[0007] Step (1): adding a mixed aqueous solution of sodium phosphate (Na3PO4) (50-100 mM) and a peptide to an ethanol solution containing a thickener, vortexing rapidly, and allowing the solution to stand to induce solvent phase separation between water and ethanol to form nanodroplets;
[0008] Step (2): adding a calcium chloride (CaCl2) (0.5-1.5 M) ethanol solution to the solvent phase separation system to react and generate calcium phosphate nanoparticles (peptide@CaP) encapsulating peptide drug molecules (e.g., semaglutide, liraglutide, tesiparatide and other diabetes therapeutic peptide drugs);
[0009] Step (3): The reaction solution is centrifuged to remove the supernatant to obtain the product, which is then washed and purified with pure water for multiple times to finally obtain purified peptide@CaP.
[0010] Preferably, the inducing solvent phase separation to form nanodroplets in step (1) is specifically prepared by preparing 1 mL of hydroxypropyl cellulose (HPC) thickener ethanol solution (1 wt%), and mixing 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of polypeptide aqueous solution (10 mg / mL) in advance. The mixed sodium phosphate-polypeptide aqueous solution is quickly added to the hydroxypropyl cellulose ethanol solution and the system is vortexed for 5 s. After vortexing, the reaction system is allowed to stand for 1 min to complete the water-ethanol solvent phase separation and form nanodroplets;
[0011] Preferably, the synthesis of peptide@CaP in step (2) is carried out by preparing a 1 M calcium chloride ethanol solution in advance, and after the standing in step (1), quickly adding 100 μL of calcium chloride ethanol solution (1 M) to the solvent phase separation system under vortexing, and after the addition is completed, placing the reaction system in a 30°C metal bath and standing for 1 h;
[0012] Preferably, the product purification process described in step (3) is specifically performed by centrifuging the mixed solution after the reaction at a speed of 14000 rmp for 15 min, discarding the supernatant, dispersing the precipitated product in pure water and continuing centrifugation, and repeating the process three times to achieve the purpose of washing and purifying the product. The purified product can be dispersed in a specific solvent or dried for subsequent characterization or application.
[0013] Preferably, the synthesis steps are as follows:
[0014] Step (1): Take 1 mL of hydroxypropyl cellulose ethanol solution (1 wt%), mix 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of polypeptide aqueous solution (10 mg / mL), and quickly add them into the mixture, and vortex for 5 s. After vortexing, let the reaction system stand for 1 min to achieve water-ethanol solvent phase separation and form nanodroplets;
[0015] Step (2): 100 μL of calcium chloride ethanol solution (1 M) was quickly added to the reaction system after standing under vortexing, and the reaction was allowed to stand in a metal bath at 30 °C for 1 h to synthesize peptide@CaP;
[0016] Step (3): After the reaction, the mixed solution was centrifuged at 14,000 rpm for 15 min, and the supernatant was removed to obtain the product precipitate. The product precipitate was dispersed with pure water and then centrifuged and washed for purification three times to finally obtain the purified peptide@CaP.
[0017] A method for synthesizing calcium phosphate nanoparticles encapsulating polypeptide drug molecules by solvent phase separation, comprising:
[0018] Step (1): inducing water-ethanol solvent phase separation and forming nanodroplets;
[0019] Step (2): Synthesis of peptide@CaP based on the formation of nanodroplets by solvent phase separation;
[0020] Step (3): Purify the product peptide@CaP with pure water.
[0021] Beneficial effects of the present invention:
[0022] (1) A platform technology for rapidly synthesizing calcium phosphate nanoparticles and encapsulating polypeptide drug molecules in a simple reaction system has been established. Under this technology, all kinds of polypeptide drug molecules can be encapsulated in calcium phosphate nanoparticles, which has high universality. In the reaction system of the present invention, due to the property that sodium phosphate is easily soluble in water but insoluble in ethanol, it is used as both a phase separation agent for the water-ethanol solvent system and a raw material for the synthesis of calcium phosphate nanoparticles, which simplifies the reaction system for synthesizing calcium phosphate nanoparticles and encapsulating polypeptide drug molecules to the greatest extent. The reaction process of this method is simple, the substances involved in the reaction system are relatively few and all have strong biocompatibility, the reaction time is short, and calcium phosphate nanoparticles (peptide@CaP) encapsulating polypeptide drug molecules can be efficiently synthesized. By adjusting the synthesis parameters, the synthesis ratio determined by the present invention can ensure a certain encapsulation rate on the basis of ensuring the particle morphology, and the calculated polypeptide encapsulation rate is above 30%.
[0023] (2) Calcium phosphate nanoparticles are used as a protective layer to protect polypeptide drug molecules, thereby improving the stability of polypeptide molecules. The calcium phosphate nanoparticles encapsulating polypeptide drug molecules obtained by the synthesis method of the present invention can effectively protect polypeptide molecules from damage in alkaline environments, strong oxidative environments, etc., and polypeptide drug molecules can be released within a certain period of time.
[0024] (3) Different from other technologies for synthesizing calcium phosphate encapsulated polypeptide drug molecules, which have complex reaction systems and long reaction times, the present invention simplifies the reaction system to the greatest extent, ensuring that calcium phosphate nanoparticles encapsulating polypeptide drug molecules can be easily synthesized, while having a short reaction time and high synthesis efficiency.
[0025] (4) Comparative Example 1 shows that the encapsulation efficiency of liraglutide is about 25%, which is lower than the encapsulation efficiency of Example 2. The product morphology is observed to be relatively uneven by transmission electron microscopy. Compared with Example 2, there are a large number of micron-sized aggregates, indicating that the morphology of the product synthesized using PVP as a thickener is relatively uncontrollable ( Figure 8 b).
[0026] (5) Comparative Example 2 shows that the product, observed by transmission electron microscopy, has an irregular granular morphology compared with Example 2, and there are more unformed flocs ( Fig. 9 b), indicating that the product synthesized using a lower concentration of sodium phosphate solution has a poor morphology.
[0027] (6) Comparative Example 3 shows that the encapsulation efficiency of liraglutide is about 16%, which is lower than the encapsulation efficiency of Example 2. The product is observed to be spherical hollow nanoparticles ( Fig.10 b). This indicates that the ability of synthesizing CaP encapsulated polypeptide drug molecules using a higher concentration of sodium phosphate solution is inferior to that of Example 2.
[0028] (7) Comparative Example 4 shows that the encapsulation efficiency of liraglutide is about 27%, which is lower than the encapsulation efficiency of Example 2. The product is observed to be spherical hollow nanoparticles ( Fig.11 b). This indicates that the ability of synthesizing CaP encapsulated polypeptide drug molecules using a lower concentration of calcium chloride ethanol solution is inferior to that of Example 2.
[0029] The encapsulation efficiency of liraglutide in Example 2 is about 31%. Through transmission electron microscopy and scanning electron microscopy, it can be observed that the product is a relatively uniform spherical hollow nanoparticle ( Figure 3 ), is the best embodiment.
[0030] The calcium phosphate nanoparticles of Example 2 can effectively protect the polypeptide molecules from being damaged by the alkaline environment. At the same time, the Lira.@CaP ( Fig.13 c), it can be found that its nanostructure has not been destroyed. Liraglutide encapsulated in calcium phosphate nanoparticles also showed a strong peptide UV absorption signal under a strong oxidative environment, indicating that calcium phosphate nanoparticles can effectively protect peptide molecules from being damaged by a strong oxidative environment. At the same time, transmission electron microscopy was used to observe Lira.@CaP ( Fig.14 c) It can be found that its nanostructure has not been destroyed.
[0031] Lira.@CaP (product of Example 2) was dispersed in a Glycine-HCl buffer solution (pH = 2.2) for release experiments. During the release process, the product precipitate gradually dissolved and was completely digested within about 48 h ( Fig.15 a) The UV absorption signal of the product digestion solution was detected by UV-visible spectrophotometer, and an obvious absorption peak of polypeptide molecules was found ( Fig.15b) It proves that the polypeptide drug molecules encapsulated by calcium phosphate nanoparticles can be released within a certain period of time. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The present invention will be further described below in conjunction with the accompanying drawings.
[0033] Figure 1 This is a diagram of the mechanism of synthesizing nanoscale calcium phosphate encapsulated peptide drug molecules using solvent phase separation.
[0034] Figure 2 It is a comparison chart of UV-visible absorption spectra of calcium phosphate nanoparticles encapsulating liraglutide (Lira.@CaP), liraglutide aqueous solution and calcium phosphate nanoparticles;
[0035] Figure 3 (a) is a transmission electron micrograph of Lira.@CaP; (b) is a scanning electron micrograph of Lira.@CaP;
[0036] Figure 4 is a comparison chart of UV-visible absorption spectra of calcium phosphate nanoparticles encapsulating semaglutide (Sema.@CaP), semaglutide aqueous solution and calcium phosphate nanoparticles;
[0037] Figure 5 (a) is a transmission electron micrograph of Sema.@CaP; (b) is a scanning electron micrograph of Sema.@CaP;
[0038] Figure 6 is a comparison chart of UV-visible absorption spectra of calcium phosphate nanoparticles encapsulating tesiparatide (Tirz.@CaP), tesiparatide aqueous solution and calcium phosphate nanoparticles;
[0039] Figure 7 (a) is a transmission electron micrograph of Tirz.@CaP; (b) is a scanning electron micrograph of Tirz.@CaP;
[0040] Figure 8 (a) is a comparison of the UV-visible absorption spectra of Lira.@CaP (PVP) and liraglutide aqueous solution; (b) is a transmission electron microscopy image of Lira.@CaP (PVP);
[0041] Fig. 9 (a) is a comparison of the UV-visible absorption spectra of Lira.@CaP (50 mM Na2PO4) and liraglutide aqueous solution; (b) is a transmission electron microscopy image of Lira.@CaP (50 mM Na2PO4);
[0042] Fig.10(a) is a comparison of the UV-visible absorption spectra of Lira.@CaP (100 mM Na2PO4) and liraglutide aqueous solution; (b) is a transmission electron microscopy image of Lira.@CaP (100 mM Na2PO4);
[0043] Fig.11 (a) is a comparison of the UV-visible absorption spectra of Lira.@CaP (0.5 M CaCl2) and liraglutide aqueous solution; (b) is a transmission electron microscopy image of Lira.@CaP (0.5 M CaCl2);
[0044] Fig.12 (a) is a comparison of the UV-visible absorption spectra of Lira.@CaP (1.5 M CaCl2) and liraglutide aqueous solution; (b) is a transmission electron microscopy image of Lira.@CaP (1.5 M CaCl2);
[0045] Fig.13 (a) is a comparison of the UV-visible absorption spectra of Lira.@CaP after being treated with sodium carbonate solution or water; (b) is a comparison of the UV-visible absorption spectra of free liraglutide after being treated with sodium carbonate solution or water; (c) is a transmission electron microscopy image of Lira.@CaP after being treated with sodium carbonate solution;
[0046] Fig.14 (a) is a comparison of the UV-visible absorption spectra of Lira.@CaP after being treated with hydrogen peroxide solution or water; (b) is a comparison of the UV-visible absorption spectra of free liraglutide after being treated with hydrogen peroxide solution or water; (c) is a transmission electron microscopy image of Lira.@CaP after being treated with hydrogen peroxide solution;
[0047] Fig.15 (a) is a photo of Lira.@CaP before and after digestion; (b) is a comparison of the UV-visible absorption spectra of the Lira.@CaP digestion solution and the liraglutide aqueous solution. DETAILED DESCRIPTION
[0048] Example 1
[0049] 200 μL of sodium phosphate aqueous solution (70 mM) was quickly added to 1 mL of hydroxypropyl cellulose (HPC) thickener ethanol solution (1 wt%), and the solution was vortexed for 5 s and then allowed to stand for 1 min. After 100 μL of calcium chloride ethanol solution (1 M) was quickly added to the mixed solution after standing under vortexing, the reaction system was placed in a metal bath at 30 °C for 1 h. After the reaction was completed, the reaction system was centrifuged at 14000 rmp for 15 min. After removing the supernatant, the product precipitate was washed and purified three times with pure water to obtain the product CaP, and the product was dispersed in pure water. The ultraviolet absorption signal of the product was detected by UV-visible spectrophotometer, and no ultraviolet absorption signal peak was found ( Figure 2 , Figure 4 , Figure 6 ).
[0050] Example 2
[0051] 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of liraglutide aqueous solution (10 mg / mL) were mixed and quickly added to 1 mL of hydroxypropyl cellulose (HPC) thickener ethanol solution (1 wt%). The mixed solution was vortexed for 5 s and then allowed to stand for 1 min. After 100 μL of calcium chloride ethanol solution (1 M) was quickly added to the mixed solution after standing under vortexing, the reaction system was placed in a metal bath at 30 °C for 1 h. After the reaction was completed, the reaction system was centrifuged at 14000 rmp for 15 min. After removing the supernatant, the product precipitate was washed and purified three times with pure water to obtain the product Lira.@CaP, and the product was dispersed in pure water. The ultraviolet absorption signal of the product was detected by UV-visible spectrophotometer and compared with the liraglutide aqueous solution. An obvious polypeptide molecule absorption peak ( Figure 2 ), verifying that the polypeptide molecules are encapsulated in CaP nanoparticles. The UV-visible absorption curve of CaP is used as the background to deduct from the UV-visible absorption curve of Lira.@CaP, and the encapsulation efficiency of liraglutide by this method is calculated to be about 31% based on the relationship between the characteristic absorption peak intensity of liraglutide solution and the concentration. Through transmission electron microscopy and scanning electron microscopy, it can be observed that the product is a relatively uniform spherical hollow nanoparticle ( Figure 3 ).
[0052] Example 3
[0053] 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of semaglutide aqueous solution (10 mg / mL) were mixed and quickly added to 1 mL of hydroxypropyl cellulose (HPC) thickener ethanol solution (1 wt%). The mixed solution was vortexed for 5 s and then allowed to stand for 1 min. After 100 μL of calcium chloride ethanol solution (1 M) was quickly added to the mixed solution after standing under vortexing, the reaction system was placed in a metal bath at 30 °C for 1 h. After the reaction was completed, the reaction system was centrifuged at 14000 rmp for 15 min. After removing the supernatant, the product precipitate was washed and purified three times with pure water to obtain the product Sema.@CaP, and the product was dispersed in pure water. The ultraviolet absorption signal of the product was detected by UV-visible spectrophotometer and compared with the semaglutide aqueous solution. An obvious polypeptide molecule absorption peak was found ( Figure 4 ). The UV-visible absorption curve of CaP was used as the background and deducted from the UV-visible absorption curve of Sema.@CaP. The relationship between the characteristic absorption peak intensity of semaglutide solution and the concentration was used to calculate that the encapsulation efficiency of semaglutide by this method was about 40%. The product was observed to be a relatively uniform spherical hollow nanoparticle by transmission electron microscopy and scanning electron microscopy ( Figure 5 ).
[0054] Example 4
[0055] 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of tesiparatide aqueous solution (10 mg / mL) were mixed and quickly added to 1 mL of hydroxypropyl cellulose (HPC) thickener ethanol solution (1 wt%). The mixed solution was vortexed for 5 s and then allowed to stand for 1 min. 100 μL of calcium chloride ethanol solution (1 M) was quickly added to the mixed solution after standing under vortexing, and the reaction system was placed in a metal bath at 30 °C for 1 h. After the reaction was completed, the reaction system was centrifuged at 14000 rmp for 15 min. After removing the supernatant, the product precipitate was washed and purified three times with pure water to obtain the product Tirz.@CaP, and the product was dispersed in pure water.
[0056] The UV absorption signal of the product was detected by UV-visible spectrophotometer and compared with the aqueous solution of tesiparatide, and an obvious absorption peak of the polypeptide molecule was found ( Figure 6 ). The UV-visible absorption curve of CaP was used as the background and deducted from the UV-visible absorption curve of Tirz.@CaP. The encapsulation efficiency of tesiparatide by this method was calculated to be about 32% based on the relationship between the characteristic absorption peak intensity of the tesiparatide solution and the concentration. The product was observed to be a relatively uniform spherical hollow nanoparticle by transmission electron microscopy and scanning electron microscopy ( Figure 7 ).
[0057] Comparative Example 1
[0058] 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of liraglutide aqueous solution (10 mg / mL) were mixed and quickly added to 1 mL of polyvinyl pyrrolidone (PVP) thickener ethanol solution (1 wt%). The mixed solution was vortexed for 5 s and then allowed to stand for 1 min. 100 μL of calcium chloride ethanol solution (1 M) was quickly added to the mixed solution after standing under vortexing, and the reaction system was placed in a metal bath at 30 °C for 1 h. After the reaction was completed, the reaction system was centrifuged at 14000 rmp for 15 min. After removing the supernatant, the product precipitate was washed and purified three times with pure water to obtain the product Lira.@CaP (PVP), and the product was dispersed in pure water. The ultraviolet absorption signal of the product was detected by UV-visible spectrophotometer and compared with the liraglutide aqueous solution. An obvious polypeptide molecule absorption peak ( Figure 8 a). The UV-visible absorption curve of CaP was used as the background and deducted from the UV-visible absorption curve of Lira.@CaP (PVP), and the encapsulation efficiency of liraglutide by this method was calculated to be about 25% using the relationship between the characteristic absorption peak intensity of the liraglutide solution and the concentration, which was lower than the encapsulation efficiency of Example 2. The product morphology was observed to be relatively uneven by transmission electron microscopy, and there were a large number of micron-scale aggregates compared with Example 2, indicating that the morphology of the product synthesized using PVP as a thickener was relatively uncontrollable ( Figure 8 b).
[0059] Comparative Example 2
[0060] 200 μL of sodium phosphate aqueous solution (50 mM) and 30 μL of liraglutide aqueous solution (10 mg / mL) were mixed and quickly added to 1 mL of hydroxypropyl cellulose (HPC) thickener ethanol solution (1 wt%). The mixed solution was vortexed for 5 s and then allowed to stand for 1 min. 100 μL of calcium chloride ethanol solution (1 M) was quickly added to the mixed solution after standing under vortexing, and the reaction system was placed in a metal bath at 30 °C for 1 h. After the reaction was completed, the reaction system was centrifuged at 14000 rmp for 15 min. After removing the supernatant, the product precipitate was washed and purified three times with pure water to obtain the product Lira.@CaP (50 mM Na2PO4), and the product was dispersed in pure water. The ultraviolet absorption signal of the product was detected by UV-visible spectrophotometer and compared with the liraglutide aqueous solution. An obvious polypeptide molecule absorption peak ( Fig. 9a). The UV-visible absorption curve of CaP was used as the background and deducted from the UV-visible absorption curve of Lira.@CaP (50 mMNa2PO4), and the encapsulation efficiency of liraglutide by this method was calculated to be about 35% based on the relationship between the characteristic absorption peak intensity of liraglutide solution and the concentration, which was slightly higher than the encapsulation efficiency of Example 2. However, the product was observed by transmission electron microscopy, and its morphology was irregular granular compared with Example 2, and there were more unformed flocs ( Fig. 9 b), indicating that the product synthesized using a lower concentration of sodium phosphate solution has a poor morphology.
[0061] Comparative Example 3
[0062] 200 μL sodium phosphate aqueous solution (100 mM) and 30 μL liraglutide aqueous solution (10 mg / mL) were mixed and quickly added to 1 mL hydroxypropyl cellulose (HPC) thickener ethanol solution (1 wt%). The mixed solution was vortexed for 5 s and then allowed to stand for 1 min. 100 μL calcium chloride ethanol solution (1 M) was quickly added to the mixed solution after standing under vortexing, and the reaction system was placed in a metal bath at 30 °C for 1 h. After the reaction was completed, the reaction system was centrifuged at 14000 rmp for 15 min. After removing the supernatant, the product precipitate was washed and purified three times with pure water to obtain the product Lira.@CaP (100 mM Na2PO4), and the product was dispersed in pure water. The ultraviolet absorption signal of the product was detected by UV-visible spectrophotometer and compared with the liraglutide aqueous solution. An obvious polypeptide molecule absorption peak ( Fig.10 a). The UV-visible absorption curve of CaP was used as the background and deducted from the UV-visible absorption curve of Lira.@CaP (100 mM Na2PO4), and the encapsulation efficiency of liraglutide by this method was calculated to be about 16% based on the relationship between the characteristic absorption peak intensity of liraglutide solution and the concentration, which was lower than the encapsulation efficiency of Example 2. The product was observed to be spherical hollow nanoparticles ( Fig.10 b). This indicates that the ability of synthesizing CaP encapsulated polypeptide drug molecules using a higher concentration of sodium phosphate solution is inferior to that of Example 2.
[0063] Comparative Example 4
[0064] 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of liraglutide aqueous solution (10 mg / mL) were mixed and quickly added to 1 mL of hydroxypropyl cellulose (HPC) thickener ethanol solution (1 wt%). The mixed solution was vortexed for 5 s and then allowed to stand for 1 min. 100 μL of calcium chloride ethanol solution (0.5 M) was quickly added to the mixed solution after standing under vortexing, and the reaction system was placed in a metal bath at 30 °C for 1 h. After the reaction was completed, the reaction system was centrifuged at 14000 rmp for 15 min. After removing the supernatant, the product precipitate was washed and purified three times with pure water to obtain the product Lira.@CaP (0.5 M CaCl2), and the product was dispersed in pure water. The ultraviolet absorption signal of the product was detected by UV-visible spectrophotometer and compared with the liraglutide aqueous solution. An obvious polypeptide molecule absorption peak ( Fig.11 a). The UV-visible absorption curve of CaP was used as the background and deducted from the UV-visible absorption curve of Lira.@CaP (0.5M CaCl2), and the encapsulation efficiency of liraglutide by this method was calculated to be about 27% based on the relationship between the characteristic absorption peak intensity of liraglutide solution and the concentration, which was lower than the encapsulation efficiency of Example 2. The product was observed to be spherical hollow nanoparticles ( Fig.11 b). This indicates that the ability of synthesizing CaP encapsulated polypeptide drug molecules using a lower concentration of calcium chloride ethanol solution is inferior to that of Example 2.
[0065] Comparative Example 5
[0066] 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of liraglutide aqueous solution (10 mg / mL) were mixed and quickly added to 1 mL of hydroxypropyl cellulose (HPC) thickener ethanol solution (1 wt%). The mixed solution was vortexed for 5 s and then allowed to stand for 1 min. 100 μL of calcium chloride ethanol solution (1.5 M) was quickly added to the mixed solution after standing under vortexing, and the reaction system was placed in a metal bath at 30 °C for 1 h. After the reaction was completed, the reaction system was centrifuged at 14000 rmp for 15 min. After removing the supernatant, the product precipitate was washed and purified three times with pure water to obtain the product Lira.@CaP (1.5 M CaCl2), and the product was dispersed in pure water. The ultraviolet absorption signal of the product was detected by UV-visible spectrophotometer and compared with the liraglutide aqueous solution. An obvious polypeptide molecule absorption peak ( Fig.12a). The UV-visible absorption curve of CaP was used as the background and deducted from the UV-visible absorption curve of Lira.@CaP (1.5M CaCl2), and the encapsulation efficiency of liraglutide by this method was calculated to be about 32% by using the relationship between the characteristic absorption peak intensity of liraglutide solution and the concentration, which was similar to the encapsulation efficiency of Example 2. However, the product was observed by transmission electron microscopy. Compared with Example 2, the product had a large amount of aggregation, and more micron-sized large particles were observed, and there were more unformed flocs ( Fig.12 b) This indicates that the product synthesized using a higher concentration of sodium phosphate solution has a poor morphology and is more uncontrollable.
[0067] Experiment 1
[0068] Lira.@CaP (product of Example 2) dispersed in 10 μL of water was added to 200 μL of sodium carbonate solution (2 M, pH = 12) or 200 μL of water. After waiting for 10 min, the UV absorption signal of the solution was detected using a UV-visible spectrophotometer ( Fig.13 a). At the same time, 10 μL of liraglutide aqueous solution was added to 200 μL of sodium carbonate solution (2 M, pH = 12) or 200 μL of water, and the UV absorption signal of the solution was detected by UV-visible spectrophotometer as a control group ( Fig.13 b). It can be clearly observed that free liraglutide no longer has characteristic UV absorption signals in the alkaline environment of sodium carbonate solution, indicating that the peptide structure has been destroyed; while liraglutide encapsulated in calcium phosphate nanoparticles still shows strong peptide UV absorption signals in the alkaline environment, indicating that calcium phosphate nanoparticles can effectively protect peptide molecules from damage in the alkaline environment. At the same time, transmission electron microscopy was used to observe the Lira.@CaP ( Fig.13 c) It can be found that its nanostructure has not been destroyed.
[0069] Experiment 2
[0070] Lira.@CaP (product of Example 2) dispersed in 10 μL of water was added to 200 μL of 3% hydrogen peroxide solution or 200 μL of water. After waiting for 10 min, the UV absorption signal of the solution was detected using a UV-visible spectrophotometer ( Fig.14 a). At the same time, 10 μL of liraglutide aqueous solution was added to 200 μL of 3% hydrogen peroxide solution or 200 μL of water, and the ultraviolet absorption signal of the solution was detected by UV-visible spectrophotometer as a control group ( Fig.14b). It can be clearly observed that free liraglutide no longer has characteristic UV absorption signals in the strong oxidizing environment of hydrogen peroxide solution, indicating that the polypeptide structure has been destroyed; while liraglutide encapsulated in calcium phosphate nanoparticles still shows strong polypeptide UV absorption signals in the strong oxidizing environment, indicating that calcium phosphate nanoparticles can effectively protect polypeptide molecules from being damaged by the strong oxidizing environment. At the same time, transmission electron microscopy was used to observe the Lira.@CaP ( Fig.14 c) It can be found that its nanostructure has not been destroyed.
[0071] Experiment 3
[0072] Lira.@CaP (product of Example 2) was dispersed in a Glycine-HCl buffer solution (pH = 2.2) for release experiments. During the release process, the product precipitate gradually dissolved and was completely digested within about 48 h ( Fig.15 a) The UV absorption signal of the product digestion solution was detected by UV-visible spectrophotometer, and an obvious absorption peak of polypeptide molecules was found ( Fig.15 b) It proves that the polypeptide drug molecules encapsulated by calcium phosphate nanoparticles can be released within a certain period of time.
[0073] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.
Claims
1. A method for synthesizing calcium phosphate nanoparticles encapsulating polypeptide drug molecules using solvent phase separation, the specific steps are as follows Step (1): adding a mixed aqueous solution of sodium phosphate (50-100 mM) and a polypeptide to an ethanol solution containing a thickener hydroxypropyl cellulose, and rapidly vortexing and standing the solution to induce solvent phase separation between water and ethanol to form nanodroplets; Step (2): adding calcium chloride (0.5-1.5 M) ethanol solution to the solvent phase separation system to react and generate calcium phosphate nanoparticles (peptide@CaP) encapsulating peptide drug molecules; Step (3): The reaction solution is centrifuged to remove the supernatant to obtain the product, which is then washed and purified with pure water for multiple times to finally obtain purified peptide@CaP.
2. The method for encapsulating polypeptide drug molecules by synthesizing calcium phosphate nanoparticles by solvent phase separation according to claim 1, characterized in that: The polypeptide drug is semaglutide, liraglutide or tesiparatide.
3. The method for encapsulating polypeptide drug molecules by synthesizing calcium phosphate nanoparticles by solvent phase separation according to claim 1, characterized in that: The inducing solvent phase separation to form nanodroplets as described in step (1) is specifically performed by preparing 1 mL of hydroxypropyl cellulose thickener ethanol solution (1 wt%) and mixing 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of polypeptide aqueous solution (10 mg / mL) in advance; the mixed sodium phosphate-polypeptide aqueous solution is quickly added to the hydroxypropyl cellulose ethanol solution and the system is vortexed for 5 s. After vortexing, the reaction system is allowed to stand for 1 min to complete the water-ethanol solvent phase separation and form nanodroplets.
4. The method for encapsulating polypeptide drug molecules by synthesizing calcium phosphate nanoparticles by solvent phase separation according to claim 1, characterized in that: The specific method for synthesizing peptide@CaP described in step (2) is to prepare a 1 M calcium chloride ethanol solution in advance, and after the standing in step (1) is completed, 100 μL of calcium chloride ethanol solution (1 M) is quickly added to the solvent phase separation system under vortexing. After the addition is completed, the reaction system is placed in a 30°C metal bath and allowed to react for 1 h.
5. The method for encapsulating polypeptide drug molecules by synthesizing calcium phosphate nanoparticles by solvent phase separation according to claim 1, characterized in that: The product purification process described in step (3) is specifically performed by centrifuging the mixed solution after the reaction at a speed of 14000 rpm for 15 min, discarding the supernatant, dispersing the precipitated product in pure water and continuing to centrifuge, and repeating the process three times to achieve the purpose of washing and purifying the product. The purified product can be dispersed in a specific solvent or dried for subsequent characterization or application.
6. The method for encapsulating polypeptide drug molecules by synthesizing calcium phosphate nanoparticles by solvent phase separation according to claim 1, characterized in that: The synthesis steps are as follows: Step (1): Take 1 mL of hydroxypropyl cellulose ethanol solution (1 wt%), mix 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of peptide aqueous solution (10 mg / mL), and quickly add them. The mixture was vortexed for 5 s, and the reaction system was allowed to stand for 1 min to achieve phase separation of water-ethanol solvent and form nanodroplets; Step (2): 100 μL of calcium chloride ethanol solution (1 M) was quickly added to the reaction system after standing under vortexing, and the reaction was allowed to stand in a metal bath at 30 °C for 1 h to synthesize peptide@CaP; Step (3): After the reaction, the mixed solution was centrifuged at 14,000 rpm for 15 min, and the supernatant was removed to obtain the product precipitate. The product precipitate was dispersed with pure water and then centrifuged and washed for purification three times to finally obtain the purified peptide@CaP.
7. The method for encapsulating polypeptide drug molecules by synthesizing calcium phosphate nanoparticles by solvent phase separation according to claim 1, characterized in that: The synthesis steps are as follows: Step (1): Take 1 mL of hydroxypropyl cellulose ethanol solution (1 wt%), mix 200 μL of sodium phosphate aqueous solution (70 mM) and 30 μL of liraglutide aqueous solution (10 mg / mL), and quickly add them. The mixture was vortexed for 5 s, and the reaction system was allowed to stand for 1 min to achieve phase separation of water-ethanol solvent and form nanodroplets; Step (2): 100 μL of calcium chloride ethanol solution (1 M) was quickly added to the reaction system after standing under vortexing, and the reaction was allowed to stand in a metal bath at 30 °C for 1 h to synthesize Lira.@CaP; Step (3): After the reaction, the mixed solution was centrifuged at 14,000 rpm for 15 min, and the supernatant was removed to obtain the product precipitate. The product was dispersed with pure water and then centrifuged and washed for purification three times to finally obtain the purified Lira.@CaP.
8. The method for encapsulating polypeptide drug molecules by synthesizing calcium phosphate nanoparticles by solvent phase separation according to claim 1, characterized in that: Calcium phosphate nanoparticles are used as a protective layer to protect polypeptide drug molecules, thereby improving the stability of polypeptide molecules. The obtained calcium phosphate nanoparticles encapsulating polypeptide drug molecules can effectively protect polypeptide molecules from damage in alkaline environments and strong oxidizing environments. At the same time, the polypeptide drug molecules encapsulated by calcium phosphate nanoparticles can be released within a certain period of time.
Citation Information
Patent Citations
Nanometer pore hydroxyl calcium phosphate / aquogel materials
CN102188754A
Mineralized exenatide release system and preparation method and application thereof
CN107412741A
Nucleic acids encoding repetitive amino acid sequences rich in proline and alanine residues that have low repetitive nucleotide sequences
CN109153996A
Core-shell calcium phosphate polypeptide composite nano vaccine and preparation method thereof
CN114306623A
Method for reliably synthesizing nano / submicron liquid drops by inducing liquid-liquid phase separation and application of nano / submicron liquid drops
CN114471750A